1995
DOI: 10.1159/000106925
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Reactivity to Acetazolamide in (Senile) Dementia of Alzheimer’s Type: Relationship to Disease Severity

Abstract: Neuropathological reports about denervation and amyloid angiopathy in dementia of Alzheimer''s type (DAT) as well as signs of selective incomplete white matter infarctions point to a vascular involvement within the degenerative process. In order to investigate potential alterations of cerebrovascular function we performed cerebral blood flow measurements before and after intravenous injection of 1 g acetazolamide using technetium-99m hexamethylpropyleneamine oxime and single photon emission tomography in 12 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 55 publications
3
14
1
Order By: Relevance
“…As in the study by Stoppe et al [93], contrasting rates of CBF increase between patients and controls revealed significant CVR CO2 differences in the frontal, parietal and temporal cortices. Baseline flow in these regions was also lower than in controls.…”
Section: Cvrco2 Studies In Adsupporting
confidence: 68%
See 1 more Smart Citation
“…As in the study by Stoppe et al [93], contrasting rates of CBF increase between patients and controls revealed significant CVR CO2 differences in the frontal, parietal and temporal cortices. Baseline flow in these regions was also lower than in controls.…”
Section: Cvrco2 Studies In Adsupporting
confidence: 68%
“…In contrast to these results, Stoppe et al [93] found a significant CVR CO2 impairment in AD. Twelve patients with AD and 9 controls were studied.…”
Section: Cvrco2 Studies In Admentioning
confidence: 65%
“…On the other hand, the hypercapnia challenge in SPECT and PET studies give ambiguous results without convincing evidence of decreased cerebrovascular reserve capacity in AD (Yamaguchi et al, 1980; Bonte et al, 1989; Kuwabara et al, 1992; Stoppe et al, 1995; Knapp et al, 1996; Jagust et al, 1997; Oishi et al, 1999; Pavics et al, 1999). However, it must be taken into account that in earlier publications, the diagnostic criteria for AD may differ from nowadays criteria and older devices may not give very accurate results (Glodzik et al, 2013).…”
Section: Transcranial Ultrasound In Admentioning
confidence: 99%
“…2,3 Most AD cases (60% to 90%) are associated with ischemic vascular disease, and 90% of AD patients exhibit cerebral amyloid angiopathy (CAA), a vascular disease caused by amyloid deposition in the vessels. 1 An association between AD and reduced vascular reactivity, a physiological consequence of CAA, was demonstrated with transcranial Doppler, [4][5][6] functional magnetic resonance imaging (fMRI), 7,8 positron emission tomography (PET), 9 and single-photon emission computed tomography (SPECT) 10 techniques. Neurovascular coupling (NVC), the localized vasodilation that occurs from a specific metabolic demand, is also reduced in AD with visual 11 and verbal fluency 12 challenges.…”
Section: Introductionmentioning
confidence: 99%